Origami-paper microfluidics device for rapid diagnostics in low-resource settings - Pan, Yuwei; Hui, Qingxin; Yang, Zhugen (Elsevier, 2026)
For microfluidics platforms used for medical diagnostics, paper-based substrates offer a low-cost, easily accessible, and environmentally friendly solution. The combination of origami-paper microfluidics with sensing techniques such as colorimetry, fluorescence, electrochemistry, and surface plasmon resonance (SPR) has expanded their applications in point-of-care testing for rapid diagnostics, public health, water quality, and environment surveillance.
Keywords: 31 Biological Sciences; 40 Engineering; 4016 Materials Engineering; Biotechnology; Health Disparities and Racial or Ethnic Minority Health Research; Health Disparities; Bioengineering; Generic health relevance